Fratelli Tutti: Brotherhood Without Boundaries - Leonardus Samosir; Mochamad Ziaul Haq (UIN Sunan Gunung Djati Bandung, 2022)
This article is the result of research on the work of Pope Francis, Fratelli tutti. Le vie della Cristianità. This is a revised version of the 66th Parahyangan Catholic University Oratio Dies Natalies, 17 January 2021 by Father Leonardus Samosir.